Unpacking Speech Acts in Political Discourse Joe Biden’s Speeches on the Hamas and Israel Conflict - Wibowo, Hanafi; Sholihah, Umi (Teaching English as Foreign Language, Literature and Linguisticss, 2025)
This study investigates the use of speech acts in Joe Biden’s 2023 speeches concerning the Hamas and Israel conflict, with a focus on identifying and interpreting the pragmatic functions of his language. Drawing on Austin’s and Searle’s framework of speech acts, the analysis categorizes utterances into locutionary, illocutionary, and perlocutionary acts, with particular emphasis on illocutionary functions. The data were collected from Biden’s public addresses and analyzed qualitatively to determine the frequency and communicative purpose of each speech act category. The findings reveal that assertive speech acts dominate the discourse (64%), followed by directives (24%), declaratives (9%), and expressives (3%), with no commissive identified. This indicates Biden’s preference for asserting information and guiding responses rather than expressing emotions or making binding commitments. Comparative analysis with previous studies such as research on Netanyahu’s crisis rhetoric, Hamas representatives’ accusatory strategies, and speech acts in films shows both similarities and differences. While assertives consistently dominate across contexts, Biden’s avoidance of commissives and limited use of expressives distinguishes his rhetoric as cautious and diplomatic. The study concludes that speech act patterns in political discourse are strongly shaped by the speaker’s role, political stance, and global positioning, offering new insights into the intersection of pragmatics and international political communication.